1994
DOI: 10.1177/036354659402200207
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Surgical Management of Arthrofibrosis After Anterior Cruciate Ligament Surgery

Abstract: We present a consecutive series of nine patients who were referred to us because of arthrofibrosis (loss of > 15 degrees of extension) after intraarticular anterior cruciate ligament reconstruction using autogenous patellar tendon (eight patients) or semitendinosus (one patient) graft. Eight patients had surgery within 2 weeks of injury. All patients had been immobilized in flexion after the anterior cruciate ligament reconstruction and they had failed to improve despite vigorous physical therapy and other clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 12 publications
4
41
1
3
Order By: Relevance
“…142,163 Patients with limited knee motion due to arthrofibrosis often complain of anterior knee pain, swelling after prolonged positions or activity, quadriceps weakness, and joint stiffness, which can result in decreased tolerance to stand, walk, or run, and difficulty returning to previous levels of activity. 112,140,159,161 Additionally, increases in patellofemoral contact pressure have been documented in knees with quadriceps or patellar tendon adhesions.…”
Section: Tablementioning
confidence: 99%
“…142,163 Patients with limited knee motion due to arthrofibrosis often complain of anterior knee pain, swelling after prolonged positions or activity, quadriceps weakness, and joint stiffness, which can result in decreased tolerance to stand, walk, or run, and difficulty returning to previous levels of activity. 112,140,159,161 Additionally, increases in patellofemoral contact pressure have been documented in knees with quadriceps or patellar tendon adhesions.…”
Section: Tablementioning
confidence: 99%
“…This complication was largely attributed to poor preoperative ROM and early surgical intervention during the infl ammatory phase of healing. 18,44,45 More recent studies have shown early surgical intervention to be safe, 3,9,20 with the best indicator of postoperative ROM loss being the patient's preoperative ROM. 30 Patients should be carefully evaluated for preoperative ROM defi cits and aggressively treated to prevent postoperative complications.…”
Section: Preoperative Rehabilitation Rmentioning
confidence: 99%
“…doi:10.2519/jospt.2007.2466 Several factors are associated with an increased risk for the development of knee extension loss following arthroscopically assisted ACLR. These include concomitant ligamentous injuries, 16 timing of surgery, 12,30,33 preoperative motion loss, 6,32 and surgical techniques, such as improper graft placement and extra-articular procedures. 12,20 Other risk factors include joint swelling and inflammation, 17 complex regional pain syndrome, 25 knee joint infection, 20 and postoperative/rehabilitation factors.…”
mentioning
confidence: 99%
“…13,27 Numerous studies have documented the importance of obtaining and maintaining full knee extension following ACLR. 26,30,32,33 Patients with limited knee extension may complain of anterior knee pain, swelling after prolonged positions or activity, crepitus at terminal knee extension, quadriceps weakness, and joint stiffness. 32 Shelbourne et al 32 have associated the inability to achieve full knee extension with poor outcomes.…”
mentioning
confidence: 99%